Modern approach to the management of genitourinary syndrome in women with gynecological malignancies - Kovačević, Nina (Radiology and oncology (Ljubljana), 2023)
The term genitourinary syndrome of menopause was first used in 2014 by the North American Menopause Society and the International Society for the Study of Women's Sexual Health to describe conditions previously known as atrophic vaginitis, urogenital atrophy, or vulvovaginal atrophy. It is a complex, chronic, progressive condition characterized by a wide range of signs and symptoms affecting sexual function and the tissues of the urinary and genital tracts. The main cause of genitourinary syndrome of menopause is estrogen deficiency caused by ovarian removal or dysfunction. The most bothersome symptoms are vaginal dryness, decreased vaginal lubrication, and pain during penetration and intercourse. They all have a negative impact on the quality of life. Conclusions: The main goal of treatment is to relieve the symptoms. Treatment modalities are pharmacological or non-pharmacological. The first-line treatment for mild to moderate symptoms is the use of personal lubricants and moisturizers, but the gold standard is estrogen replacement therapy. Hormone therapy may not be an option for women with hormone-dependent cancer.
Keywords: genitalno-urinarni sindrom; genitourinary syndrome; ginekološki raki; gynecological malignancies; onkološko zdravljenje; therapy